Institutional design in post-communist societies rebuilding the ship at sea - Elster, Jon. (Cambridge Cambridge University Press, 1998)
This book examines the problems and issues facing formerly communist states as they seek to develop a new democratic political order and a market economy. Studies of Bulgaria, the Czech Republic, Hungary and Slovakia provide detailed empirical data concerning constitution making, the shaping of democratic institutions, marketization of the economy, and social policy. This new research is then linked to innovative theoretical material to offer a unique assessment of the difficulties of creating a new political order in the region.
Includes bibliographical references (p. 309-345) and index.
Keywords: Democracy--Europe, Eastern